Organic Heterogeneities in Foraminiferal Calcite Traced Through the Distribution of N, S, and I Measured With NanoSIMS: A New Challenge for Element-Ratio-Based Paleoproxies? - Glock, Nicolaas; Liebetrau, Volker; Vogts, Angela; Eisenhauer, Anton (Frontiers in Earth Science, 2019)
Oceanic oxygen decline due to anthropogenic climate change is a matter of growing concern. A quantitative oxygen proxy is highly desirable in order to identify and monitor recent dynamics as well as to reconstruct pre-Anthropocene changes in amplitude and extension of oxygen depletion. Geochemical proxies like foraminiferal I/Ca ratios seem to be promising redox proxies. Nevertheless, recent studies on microanalyses of benthic foraminiferal I/Ca ratios at the Peruvian Oxygen Minimum Zone (OMZ) measured with Secondary-Ion-Mass-Spectrometry (SIMS) revealed a possible association of iodine with organic accumulations within the test. Here we present a new study on the micro-distribution of nitrogen, sulphur and iodine within the test-walls of Uvigerina striata from the Peruvian OMZ measured with Nano-SIMS. A quantification of the foraminiferal I/Ca ratios from our NanoSIMS study is in good agreement with quantitative results from a previous SIMS study. Additionally, we compared uncleaned specimens with specimens that have been treated with an oxidative cleaning procedure. Both nitrogen and sulfur, which are used as tracer for organic matter, show a patchy distribution within the test walls of the uncleaned specimens and a statistically significant correlation with the iodine distribution. This patchy organic rich phase has a different geochemical signature than the pristine calcitic parts of the test and another phase that shows a banding like structure and that is characterized by a strong sulfur enrichment. All three elements, sulfur, nitrogen and iodine, are strongly depleted in the cleaned specimens, even within the massive parts of the test walls that lack the connection with the test pores. These results indicate that the organic parts of the test walls are located inside a microporous framework within the foraminiferal calcite. This has to be considered in the interpretation of geochemical proxies on foraminiferal calcite, especially for microanalytical methods, since the chemical signature of these organic parts likely alters some element to Calcium ratios within the foraminiferal test.